2020
DOI: 10.1080/02673843.2020.1767662
|View full text |Cite
|
Sign up to set email alerts
|

How young female adolescents understand their pubertal body changes and reproductive system

Abstract: Purpose: This study explored young female adolescents' understanding of pubertal body changes and knowledge of their reproductive system. Method: Female students in grades seven, eight and nine were recruited from eight junior high schools in Kupang. Body mapping was conducted together with a semi-structured interview. Data was analysed using inductive thematic analysis. Result: Participants listed their pubertal body changes and then located the female reproductive system on body maps. Participants aware the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…The findings of the present study is supported by results of a study done by Deshmukh et al [16] and Sandhya and Panthee [5] who found poor pretest knowledge among adolescents regarding growing up which improved significantly after the intervention. This validates the point that if a better understanding of the changes occurring during puberty is developed, it will help in laying good foundation for the reproductive health, especially for girls [20]. Also a review study by Bhanu and Anuradha [21] revealed that adolescent girls should be equipped with the right information regarding pubertal changes, which would eventually leads to better reproductive health as well as future motherhood.…”
Section: Socio-demographic Profilesupporting
confidence: 62%
“…The findings of the present study is supported by results of a study done by Deshmukh et al [16] and Sandhya and Panthee [5] who found poor pretest knowledge among adolescents regarding growing up which improved significantly after the intervention. This validates the point that if a better understanding of the changes occurring during puberty is developed, it will help in laying good foundation for the reproductive health, especially for girls [20]. Also a review study by Bhanu and Anuradha [21] revealed that adolescent girls should be equipped with the right information regarding pubertal changes, which would eventually leads to better reproductive health as well as future motherhood.…”
Section: Socio-demographic Profilesupporting
confidence: 62%